Host angiogenic reprogramming by Echinococcus multilocularis protoscoleces protein via PDGFR/PI3K/AKT cascade - Bi, Xiaojuan; Yang, Ning; Ke, Ying; Xue, Junlong; Zhang, Xue; Liu, Hui; Chu, Jin; Li, Liang; Shao, Yingmei; Lü, Guodong; Aji, Tuerganaili; Lin, Renyong (Frontiers in Microbiology, 2025)
BackgroundAlveolar echinococcosis (AE) is a globally present zoonotic disease caused by Echinococcus multilocularis (E. multilocularis) infection, characterized by the formation of tumor-like growths primarily in the liver, with the potential to spread to other organs. Similar to tumors, E. multilocularis infection is accompanied by pathological angiogenesis, suggesting that the implementation of anti-angiogenic therapeutic strategies may also have promising applications in the treatment of AE. However, the mechanism of angiogenesis in AE remains unclear and has not been fully elucidated.ResultsIn this study, we discovered that angiogenesis related genes are significantly up-regulated in the mouse model of E. multilocularis infection and pathological angiogenesis around the lesion was significantly increased at 10–12 weeks after infection compared to the control group. Interventions utilizing a range of inhibitors at the in vitro level, including the PDGFR-β inhibitor AG1296, the PI3K inhibitor LY294002, the AKT inhibitor MK2206, and the FAK inhibitor Y15, demonstrated that E. multilocularis protoscoleces protein (EmP) induces angiogenesis through PDGFR/PI3K/AKT/FAK signaling pathway.ConclusionOur findings provide new perspectives on how E. multilocularis infection triggers pathological angiogenesis in the host liver, and may provide a novel anti-angiogenic therapeutic strategy against E. multilocularis infection.